The immunological and molecular diagnosis of toxoplasmosis (Journal of the College of Basic Education, 2022)
The present study was adopted to investigate diagnostic methods for the ocular toxoplasmosis cause by the infection with parasite Toxoplasma gondii, by different methods which included two serological methods (Latex and ELISA) and one molecular method (conventional PCR) which targeted the gene B1.The ratio of diagnosis for Latex test was 100% to ocular toxoplasmosis group, while it was negative with 100% percentage in uveitis patients group. The positive results in control group were 35.7 % and the significant difference between the three groups (p <0.01). As results of the ELISA tests also recorded significant differences (p <0.01) between the study groups where the percentages of positive results in ocular toxoplasmosis group 84% opposite 31.1% in uveitis group. The control group recorded 41.7% positive results and renamed as asymptomatic toxoplasmosis group. The mean of IgG antibody titer in ocular toxoplasmosis group was 1.661 ± 0.187 I.U./ml. which was the top among the rest groups, as well as the IgM antibody titer in this group which 1.922±0.51 I.U./ml. The results of conventional PCR test were 10 positive results in ocular toxoplasmosis group with 23.8% percentage while uveitis and asymptomatic toxoplasmosis recorded three positive results only with 21.4% and 8.6%, respectively, with no significant differences for the record those ratios between the study groups (p <0.199). It has been shown by the above results that the ELISA assay shows positive results for the Ocular Toxoplasmosis infection at a higher percentages and significant difference compared to a record of the results by using Conventional PCR for gene B1.